Evaluation of the Impact of Monetary Policy on the Financial Performance of Manufacturing Companies: Implications of Interest Rates, Inflation and Macroeconomic Stability - Fredy Arios Tiblola; Agustinus Biay; Harum Putri Prawitaningrum; Rahma K Lakamudi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This study aims to evaluate the impact of monetary policy on the financial performance of manufacturing companies in Indonesia, emphasising the implications of interest rates, inflation, and macroeconomic stability. Using a quantitative approach through multiple regression analysis, this study analyzes the relationship between monetary policy variables of Bank Indonesia's benchmark interest rate, inflation rate, exchange rate, foreign exchange reserves, and budget deficit with the company's financial performance, as measured using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Secondary data used in this study include the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015-2023. The study results indicate that the benchmark interest rate has a significant negative effect on ROA and ROE. In contrast, the inflation rate shows varying impacts on NPM and other financial performance. In addition, macroeconomic stability is measured through indicators of the rupiah exchange rate against the USD, foreign exchange reserves, and budget deficit, which significantly affect the company's financial performance. These findings emphasize the importance of monetary policy and macroeconomic stability in determining the profitability of manufacturing companies in Indonesia. This study implies that corporate management needs to develop more adaptive strategies to deal with fluctuations in monetary policy and macroeconomic conditions. In addition, policymakers need to consider the long-term impact of monetary policy on the manufacturing sector to create an economic environment conducive to industrial growth. This study contributes significantly to the literature on the impact of monetary policy on corporate financial performance in emerging markets.